Significance of the speed of internationalisation for born global firms - a multiple case study approach. (2016) - Neubert, Michael
This article analyses the significance of the speed of internationalisation for born global firms (BGFs). In this multiple case study, BGFs are defined as high-tech start-up firms (HSFs) from a small and open economy (SMOPEC) like Switzerland. The theoretical framework consists of the Uppsala internationalisation process model and BGF theory. A sample of 20 subject matter experts (SME) is interviewed. The results of this study show that the significance of the speed of internationalisation of HSFs is considered essential for the survival of HSFs from SMOPECs. Consequently, all SMEs included early and fast internationalisation in their business plans and built their business models accordingly.